Plankton Community Structure as Bioindicator Trophic Status of Jatigede Reservoir Waters - Rosadi Rosadi; Muhammad Musa; Tri Djoko Lelono (Research Journal of Life Science, 2020)
Jatigede Reservoir in Sumedang Regency is a land mass planning designed as a multi-function reservoir. The main water source for this reservoir is from Cimanuk River, which flows through Garut Regency, and has many industrial activities around the river flow. This research was conducted to assess the trophic status of water pollution in Jatigede Reservoir by utilizing plankton as a bioindicator agent. Samples were collected from 9 observation stations from November 2018 until January 2019. The results showed that 26 species of phytoplankton from 7 divisions including Dinophyta, Cyanophyta, Chlorophyta, Chrysophyta, Euglenophyta, Bacillariophyta, and Charophyta was found in Jatigede Reservoir at about 461 ind/m3. Zooplankton abundance of 6 species from 2 divisions of Rotifera and Copepoda at 2 ind/m3. The average phytoplankton diversity index was 0.93 and zooplankton diversity index was 0.23. The average phytoplankton evenness index was 0.44 and zooplankton evenness index was 0.24. The average dominance of phytoplankton was 0.58 and dominance of zooplankton was 0.25. Based on the plankton community structure, the trophic status of Jatigede Reservoir was classified to moderate polluted (eutroph) to heavily pollutants (hypereutroph). The dominant species was Perinidium sp from Dinophyta division.